Academic Supervision, Work Motivation, and Collaborative Learning Practices in Enhancing Teacher Performance at Public Senior High Schools in Berau Regency - Sitorus, ellen; Haeruddin, Haeruddin (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This comprehensive study examines the influence of academic supervision, work motivation, and collaborative learning practices on teacher performance in three public senior high schools in Berau Regency. Using a quantitative approach with cluster random sampling, the research involved 159 teachers from three accredited